Development of a Perceived Access Inventory for Community Care Mental Healthcare Services for Veterans. Issue 7 (23rd January 2019) - Pyne, Jeffrey M; Kelly, P Adam; Fischer, Ellen P; Miller, Christopher J; Wright, Patricia; Zamora, Kara; Koenig, Christopher J; Stanley, Regina; Seal, Karen; Fortney, John C
Abstract: Introduction: Access to high-quality healthcare, including mental healthcare, is a high priority for the Department of Veterans Affairs (VA). Meaningful monitoring of progress will require patient-centered measures of access. To that end, we developed the Perceived Access Inventory focused on access to VA mental health services (PAI-VA). However, VA is purchasing increasing amounts of mental health services from community mental health providers. In this paper, we describe the development of a PAI for users of VA-funded community mental healthcare that incorporates access barriers unique to community care service use and compares the barriers most frequently reported by veterans using community mental health services to those most frequently reported by veterans using VA mental health services. Materials and Methods: We conducted mixed qualitative and quantitative interviews with 25 veterans who had experience using community mental health services through the Veterans Choice Program (VCP). We used opt-out invitation letters to recruit veterans from three geographic regions. Data were collected on sociodemographics, rurality, symptom severity, and service satisfaction. Participants also completed two measures of perceived barriers to mental healthcare: the PAI-VA adapted to focus on access to mental healthcare in the community and Hoge's 13-item measure. This study was reviewed and approved by the VA Central Institutional Review Board. Results: Analysis of qualitative interview data identified four topics that were not addressed in the PAI-VA: veterans being billed directly by a VCP mental health provider, lack of care coordination and communication between VCP and VA mental health providers, veterans needing to travel to a VA facility to have VCP provider prescriptions filled, and delays in VCP re-authorization. To develop a PAI for community-care users, we created items corresponding to each of the four community-care-specific topics and added them to the 43-item PAI-VA. When we compared the 10 most frequently endorsed barriers to mental healthcare in this study sample to the ten most frequently endorsed by a separate sample of current VA mental healthcare users, six items were common to both groups. The four items unique to community-care were: long waits for the first mental health appointment, lack of awareness of available mental health services, short appointments, and providers' lack of knowledge of military culture. Conclusions: Four new barriers specific to veteran access to community mental healthcare were identified. These barriers, which were largely administrative rather than arising from the clinical encounter itself, were included in the PAI for community care. Study strengths include capturing access barriers from the veteran experience across three geographic regions. Weaknesses include the relatively small number of participants and data collection from an early stage of Veteran Choice Program implementation. As VA expands its coverage of community-based mental healthcare, being able to assess the success of the initiative from the perspective of program users becomes increasingly important. The 47-item PAI for community care offers a useful tool to identify barriers experienced by veterans in accessing mental healthcare in the community, overall and in specific settings, as well as to track the impact of interventions to improve access to mental healthcare.